Tending operation model for red oak stands - Rédei, Károly; Keserű, Zsolt; Csiha, Imre; Rásó, János; Kovács, Csaba; Antal, Borbála (Acta Agraria Debreceniensis, 2017)
Red oak (Quercus rubra L.) is our most important exotic oak species, that possesses growing culture with almost one hundred years in our country. Plantation character of red oak growing predominates principally by applied regeneration method (mostly artificial), regular planting space, applying defined method and planting space regulation system. Forest tending model for red oak, that considered stopgap in the native literature is intended to serving the latter. Especially important equation in the viewpoint of stand growing, that describes relationship of stem number (N, in hectare) and diameter at breast height (D1.3 in cm) is: N=e9.80220-1.12607lnD1.3.